Non-compulsory Instrumental Music Education in Poland and Norway - Katarzyna Julia Leikvoll (Nordic Journal of Comparative and International Education, 2025)
This article compares non-compulsory instrumental music education systems in Norway and Poland, by describing their organisation, accessibility, educational goals, curriculum framework, and the target group, and discussing consequences the chosen form of organisation and vision might have for the users. The analysis of government documents and statistics shows that while Polish Music Centres and Norwegian Schools of Music and Performing Arts offer similar instrumental education for their users, in Poland there is also a highly specialised system of music schools providing goal-oriented professional tuition for young people at all educational levels. Analysis of the target groups and curriculum frameworks reveals that the concept of music school is understood differently in the two countries. Polish music schools prepare students to become musicians and do not serve as a leisure activity, in contrast to Norwegian Schools of Music and Performing Arts, which do not make strict demands of commitment and goal-oriented participation. Poland’s system is more structured and standardised, potentially leading to high levels of technical and musical proficiency, while Norway’s system is more flexible and inclusive, promoting broader educational and personal development goals.